The TRPA1 Channel in the Cardiovascular System: Promising Features and Challenges - Zhen Wang; Zhen Wang; Zhen Wang; Di Ye; Di Ye; Di Ye; Jing Ye; Jing Ye; Jing Ye; Menglong Wang; Menglong Wang; Menglong Wang; et al. (Frontiers in Pharmacology, 2019)
The transient receptor potential ankyrin 1 (TRPA1) channel is a calcium-permeable nonselective cation channel in the plasma membrane that belongs to the transient receptor potential (TRP) channel superfamily. Recent studies have suggested that the TRPA1 channel plays an essential role in the development and progression of several cardiovascular conditions, such as atherosclerosis, heart failure, myocardial ischemia–reperfusion injury, myocardial fibrosis, arrhythmia, vasodilation, and hypertension. Activation of the TRPA1 channel has a protective effect against the development of atherosclerosis. Furthermore, TRPA1 channel activation elicits peripheral vasodilation and induces a biphasic blood pressure response. However, loss of channel expression or blockade of its activation suppressed heart failure, myocardial ischemia–reperfusion injury, myocardial fibrosis, and arrhythmia. In this paper, we review recent research progress on the TRPA1 channel and discuss its potential role in the cardiovascular system.